The Influence of Interest-to-EBITDA on Interest Deductibility Limitation as a Measure to Prevent Tax Avoidance (Empirical Study on Companies Listed on the IDX Quality 30 Index of the Indonesia Stock Exchange) - Sarah, Mauli Afra; Saleh, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of interest-to-EBITDA ratio on interest expense restrictions. This type of research is quantitative research using secondary data, namely financial statements obtained from the official website of the Indonesia Stock Exchange (IDX). The population in this study is the IDX Quality Index 30 and there are 20 companies as research samples. The sampling technique uses nonprobability sampling technique with Purposive Sampling method. The data analysis method in this study uses simple linear analysis using Excel and SPSS 20 applications. The results of this study show that the interest-to-EBITDA ratio has no effect on tax avoidance.